Barriers and Facilitating Factors Influencing Physical Activity Level Among the Universiti Malaysia Sarawak Staff - Yassimear, Ugak (Universiti Malaysia Sarawak (UNIMAS), 2020)
Introduction: Physical activity is known to have numerous health benefits which include the physical, mental and social wellbeing of the population. However, despite the frequent emphasis on the importance and benefits of being physically active, the number of populations engaged in regular physical activity is still on the low side. Barriers and facilitating factors can influence the behavioural changes in physical activity level. This study aims to identify the factors that can influence physical activity levels among the University Malaysia Sarawak (UNIMAS) staff. Method: This was a cross-sectional study using a self-administered questionnaire distributed through Google Form (online). The link for the questionnaire was disseminated to the participants using emails or QR codes. A total of 163 of UNIMAS staffs comprising of 37.4% academician and 62.2% non-academician participated in this study. The participants were selected using a multistage sampling method. Multiple logistic regression was performed to examine the factors associated with physical activity level. Result: Majority of the respondents were female (74.2%), Malays (60.1%), married (65.5%), non-academic staffs (62.6%), had tertiary education (85.9%) with mean working hours per day of 8.25 hours. PA level measured by IPAQ shows the majority of respondents had a moderate PA level (56.4%), followed by a high PA level (33.7%) and a low PA level (9.8%). There were significant findings on the association between exercise attitude barrier (p=0.003) and self-efficacy (p=0.009) with physical activity level. MLR analysis showed that exercise attitude barrier (OR=1.170, 95% CI=1.027, 1.334, p=0.019) and self-efficacy (OR= 1.091, 95% CI= 1.015, 1.172, p=0.017) was associated with low and moderate PA level Conclusion: The finding indicated that exercise attitude barrier and self-efficacy influence the outcome of physical activity level among the respondents.